2021
DOI: 10.1016/j.scs.2020.102577
|View full text |Cite
|
Sign up to set email alerts
|

Living environment matters: Unravelling the spatial clustering of COVID-19 hotspots in Kolkata megacity, India

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 78 publications
(101 reference statements)
4
69
0
2
Order By: Relevance
“…For example, our results show that increased adequacy of medical practitioners can mitigate pandemic disaster vulnerability in high density cities (shown by the negative coefficients for the interaction term), but cannot achieve the similar effects for large-scale economic activity. Moreover, how urban characteristics interplay with other socioeconomic factors (including poverty and income) that have strong influence on severety of outbreak and how these factors should be considered in urban planning, design and governance, are subject to future investigation ( Das et al, 2021 ; Sannigrahi, Pilla, Basu, Basu, & Molter, 2020 ; Silva et al, 2021 ; Wang, 2021 ).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…For example, our results show that increased adequacy of medical practitioners can mitigate pandemic disaster vulnerability in high density cities (shown by the negative coefficients for the interaction term), but cannot achieve the similar effects for large-scale economic activity. Moreover, how urban characteristics interplay with other socioeconomic factors (including poverty and income) that have strong influence on severety of outbreak and how these factors should be considered in urban planning, design and governance, are subject to future investigation ( Das et al, 2021 ; Sannigrahi, Pilla, Basu, Basu, & Molter, 2020 ; Silva et al, 2021 ; Wang, 2021 ).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…This result was expected since (a) COVID-19 started and is still concentrated mostly in big cities in the study area, and (b) there is significant evidence from literature associating higher urbanization with worst respiratory and cardiovascular health, as presented in section 1 . Studies including Kodera et al (2020) in Japan, Das et al (2021) in Kolkata, India, Li et al (2021) in Huangzhou, China, and Mansour et al (2021) in Oman, already show an association between urban parameters, such as population density, and COVID-19.…”
Section: Discussionmentioning
confidence: 96%
“…Aside from the physical restriction measures imposed by local and federal governments, other potential municipal-level factors associated to dynamic of the disease could be existing socio-economic inequalities. The empirical evidence of Das et al (2020) showed that COVID-19 spread grow exponentially in those Indian regions with large socio-economic deprivation. Similarly, the evidence comparing United Kingdom regions (Sun et al, 2020b) revealed important geographical disparities in risk and outcomes of the disease.…”
Section: Discussionmentioning
confidence: 99%